Analiza modificărilor legislative vizând procedura abreviată - Țoncu, Sanda (CEP USM, 2024)
We emphasize that the research of the simplified procedure of the trial of criminal cases based on the evidence administered during the criminal investigation phase in the domestic criminal procedural doctrine gained an impetus through Law no. 66 of April 5, 2012, implemented from October 27, 2012, which supplemented the Criminal Procedure Code with art. 364/1, thus regulating the trial procedure of the criminal case based on the evidence administered during the criminal investigation phase. This procedure represented a new way of judging criminal cases through a simplified procedure, opening new ways and perspectives for scientific research. Over the years, in the period 2012-2023, the criminal procedural law, regarding the abbreviated procedure, did not have sufficient and clear regulations, substantially complicating the activity of the courts, leaving without adequate coverage a wide spectrum of questions on the side concerned. It should be noted that currently, the multiple loopholes of the criminal procedure law regarding the procedure for adjudicating criminal cases based on the evidence administered in the criminal investigation phase provided for in art. 364/1 of the Code of Criminal Procedure are not removed, and the legislative amendments dated February 15, 2018 and April 14, 2023 are insufficient, lacking legal reasoning and late.
ANALYSIS OF LEGISLATIVE CHANGES CONCERNING THE ABBREVIATED PROCEDURE
Keywords: procedură abreviată; procedură simplificată; procedură pe baza probelor